Exploring patient involvement in obstetrics and gynaecology education for medical students: a scoping review protocol - Mary Higgins; Clare Kennedy; Shahad Al-Tikriti; Karima Ali Abubakr; Amy C O'Higgins; Jonathan P McNulty; Naomi Cooney; Suzanne Donnelly (BMJ Open)
Introduction It is important to incorporate the patient perspective into healthcare education, as we know that patients are experts in their own conditions. The expertise gained through lived experience serves to complement the theoretical knowledge that healthcare educators can provide. This scoping review aims to explore patient involvement in medical education within obstetrics and gynaecology, a specialty that can provide unique challenges and complexities to patient involvement due to its potentially highly sensitive and intimate nature. The goal of this study is to map the available literature on this topic which will allow for the identification of potential gaps in the provision of training for medical students in this field. The research also aims to highlight challenges that may be associated with patient involvement in this specialty in order to guide future initiatives.Methods and analysis The Joanna Briggs Institute scoping review framework and methodology will be used to guide and conduct this scoping review. A systematic search of electronic databases MEDLINE, CINAHL, Embase, Scopus, PsycINFO, ERIC, Google Scholar, Web of Science, African Journals Online, Cochrane Library and SciVerse will be carried out. Articles will be limited to the English language. No geographical limitations will be placed on the search. Literature from 1960 to 2023 will be considered for inclusion which corresponds with the first reports of patient educators used to assist with the demonstration of clinical skills in obstetrics and gynaecology. Relevant academic journals will be hand-searched for the previous 5 years. Identified studies will be screened by two independent reviewers and data extraction carried out by the primary researcher. Key findings will be presented in tables and summarised in narrative form. Findings from the review will be reported according to the PRISMA Extension for Scoping Reviews reporting checklist.Ethics and dissemination Ethical approval is not required for this study. The findings from the study will be submitted for publication in peer-reviewed journals and at medical education conferences.